Engineering a Future Curriculum for Technological Innovation in light of the Requirements of Digital Economy - AlShami, Ghadah Shaker Mohammed; AlZakari, Mohammed Ibrahim Abdullah (Dirasat: Educational Sciences, 2020)
This study came to engineer a curriculum proposal foreseeing the future of technological innovation and technical activities (artificial intelligence, software industry, etc.). In light of the requirements of the digital economy to high school, the purpose of this study is to determine the requirements of the digital economy in future proposed curricula. Foreseeing the future of curricula in the field of technological innovation according to script and style is one of the methods of future studies for educational planning and the design of a proposed curriculum in technological innovation scenario best suited to the curriculum is a central topic in much research. The results of the study revealed statistically significant differences between measurements and dimensional measurements degrees at the level of 0.05 or less. The study recommends the involvement of the private sector in providing technological innovation and support in all forms, and foster innovative environment across multiple channels of communication.